Protective Role of Melatonin Against Postmenopausal Bone Loss via Enhancement of Citrate Secretion From Osteoblasts - Da, Wacili; Tao, Lin; Wen, Kaicheng; Tao, Zhengbo; Wang, Shaojie; Zhu, Yue (Frontiers in Pharmacology, 2020)
A negative correlation exists between the severity of osteoporosis and citrate levels in bone. Our previous research found that melatonin can significantly improve bone mass in mice with osteoporosis, but the underlying mechanism involving citrate remains unknown. Herein, we demonstrated that melatonin increased bone volume and citrate levels in ovariectomized osteoporosis mice. Melatonin increased citrate and mineralized nodules in osteoblasts induced from primary mouse bone marrow mesenchymal stem cells in vitro. ZIP-1 knockdown and overexpression confirmed that melatonin specifically upregulated ZIP-1 to rescue citrate levels and bone mass. In general, we verified that melatonin can improve bone mass by enhancing matrix mineralization, which is highly related to increased citrate secretion from osteoblasts, and that ZIP-1 is the target of melatonin. These findings reveal another role of melatonin in regulating bone remodeling and provide a research base for its possible application in the treatment of clinical osteoporosis in the future.